On Original Sin. (1st June 2015) - Crisp, Oliver D.
Abstract This article sets out a constructive account of original sin that attempts to take seriously the Christian tradition (particularly, the Reformed tradition), and that avoids the serious theological drawback of the doctrine of original guilt. I dub this account the moderate Reformed doctrine of original sin. I also argue that an adequate understanding of original sin must be open‐textured enough to accommodate some version of the story of evolutionary human development. Although I do not offer an account of how original sin is consistent with evolutionary human development, the doctrine set out here is commensurate with several live options on this controversial theological topic, which I take to be a strength, rather than a weakness, of the view.